Kecurigaan rapid progressive glomerulonephritis akibat nefropati IgA : Sebuah laporan kasus - Kadek Anggiswari Pradnya Angela; I Nyoman Sutarka (Intisari Sains Medis, 2022)
Introduction: Clinical features of IgA nephropathy (IgAN) vary widely from asymptomatic hematuria, gross hematuria, and nephrotic range proteinuria to Rapid Progressive Glomerulonephritis (RPGN). RPGN is a challenge in itself in its diagnostic and treatment, especially in conditions of inadequate resources and facilities Case Description: Male, 52 years old, with complaints of uremia, oliguria, and leg edema. Obtained hypertension with blood pressure 159/91 mmHg. Urinalysis found +4 protein, full erythrocyte sediment, and positive erythrocyte cast. Albumin to Creatinine Ratio (ACR) levels 2163.10 g/mg creatinine. Blood Urea Nitrogen levels were 78.3 mg/dL, serum creatinine 5.11 mg/dL, serum IgA 546 mg/L, albumin, lipid profile and urological ultrasound were normal. The patient was diagnosed with acute glomerulonephritis due to IgA nephropathy with RPGN. The therapy was given Methylprednisolone 2x16mg for one month, followed by alternating days, Lisinopril 1x5mg, and Atorvastatin 1x20mg. One month of treatment follow-up showed general condition improvement, normal blood pressure, serum creatinine 1.69 mg/dL, urinalysis of erythrocyte sediments 5-10/LPB with ACR levels of 486.44 µg/mg creatinine. Discussion: RPGN is acute glomerulonephritis with a sudden, rapid, and progressive decline in renal function, accompanied by oliguria, edema, hypertension, and active urine sediment. The suspicion of RPGN, in this case, was based on the findings of nephritic symptoms and signs in the form of microscopic hematuria, erythrocyte casts, subnephrotic proteinuria, hypertension, edema, oliguria, uremia and serum creatinine increased more than two times normal. With the administration of corticosteroids, kidney function improved rapidly. A kidney biopsy was not performed due to limited human resources and facilities. Conclusion: We report a case of a 52-year-old man with acute glomerulonephritis whose clinical picture is suspected of being RPGN due to IgAN. The response to therapy is quite good with the administration of corticosteroids, ACE-I and statins.   Pendahuluan : Gambaran klinis nefropati IgA (IgAN) sangat bervariasi dari hematuria asimptomatik, gross hematuria, nephrotic range proteinuria hingga Rapid Progressive Glomerulonephritis (RPGN). RPGN merupakan tantangan tersendiri dalam diagnostik dan penanganannya, khususnya pada kondisi sumber daya serta fasilitas yang tidak memadai Deskripsi Kasus:  Laki-laki, 52 tahun dengan keluhan uremia, oligouria, dan edema tungkai. Didapatkan hipertensi dengan tekanan darah 159/91 mmHg. Urinalis didapatkan protein +4, sedimen eritrosit penuh, eritrosit cast positif. Kadar Albumin to Creatinine Ratio (ACR) 2163,10 µg/mg kreatinin. Kadar Blood Urea Nitrogen (BUN) 78,3 mg/dL, serum kreatinin 5,11 mg/dL, IgA serum 546 mg/L, serta albumin, lipid profil dan USG urologi normal. Penderita didiagnosis dengan glomerulonefritis akut oleh karena nefropati IgA dengan RPGN. Pasien diberikan metilprednisolon 2x16mg selama 1 bulan dilanjutkan alternating day, lisinopril 1x5mg, dan atorvastatin 1x20mg. Hasil follow-up 1 bulan pengobatan menunjukkan kondisi umum membaik, tekanan darah normal, serum kreatinin 1,69 mg/dL, urinalisis sedimen eritrosit 5-10 /LPB dengan kadar ACR 486,44 µg/mg kreatinin. Diskusi: RPGN adalah salah satu jenis glomerulonefritis akut dengan manifestasi penurunan fungsi ginjal mendadak, cepat, dan progresif, disertai oliguria, edema, hipertensi, serta urin sedimen aktif. Kecurigaan RPGN pada kasus ini didasarkan atas ditemukannya gejala dan tanda nefritik berupa hematuria mikroskopik, eritrosit cast, proteinuria subnefrotik, hipertensi, edema, oligouria, uremia dan serum kreatinin meningkat lebih 2 kali normal, serta dengan pemberian kortikosteroid fungsi ginjal cepat membaik. Biopsi ginjal tidak dilakukan karena keterbatasan tenaga dan sarana. Simpulan: Dilaporkan kasus laki-laki 52 tahun dengan glomerulonefritis akut yang gambaran klinisnya dicurigai sebagai RPGN karena IgAN. Respon terapi cukup baik dengan pemberian kortikosteroid, ACE-I dan statin.